Flexible Inserts for Injection Molding of Complex Micro‐Structured Polymer Components. Issue 9 (12th June 2021) - Hamilton, Alex; Perris, Jack; Convery, Neil; Mulvihill, Daniel M.; Gadegaard, Nikolaj
Abstract: Mass production of microfluidic devices commonly relies on injection molding. Injection molding requires a master surface made using micro or nanofabrication. Conventionally, electroplating from a silicon master is used for mold insert production, but this is expensive and cannot be used with masters produced via the Bosch process as interlocking of the scalloping between polymer and metal insert hinders part ejection. Here, an alternative to the electroplating process is developed by adapting a nanoimprint route to produce flexible micro‐structured polymer inserts capable of molding using a Bosch process‐produced master. An optimized fabrication approach using silicon masters with smooth sidewalls (produced using the mixed process) is used to characterize the limits of the process. Aspect ratios of 1 and below are successfully replicated. Feature spacings down to 20 µm are successfully produced with minimal variation between repeated parts. Masters produced using two different Bosch etches exhibiting both coarse and fine nanometer scalloping are also studied. Parts are successfully ejected with retained nanometer scalloping in all samples although inlay damage occurred after >10 replicas. A proof‐of‐concept microfluidic device is successfully produced vindicating the use of this approach as an efficient and cost‐effective approach for the rapid prototyping of complex micro‐structured designs. Abstract : A novel fabrication method adapted from the nanoimprint approach is developed to produce flexible inlays for injection molding of complex micro‐structured polymer surfaces. Molding from mixed etch produced masters is successfully demonstrated. A key advantage is ease of part ejection: allowing successful part ejection even for Bosch etch produced masters. Advantages for microfabrication in areas such as microfluidics are outlined.